SP10.1.4 COVID as a driver of innovation: getting the right patient to the right place at the right time. A novel Registrar-led approach to minimising unnecessary footfall in the Surgical Assessment Unit of a District General Hospital. (28th October 2021) - Court, Emma L.; Lennon, Nicola A.; Zarka, Anas; Pryor, Megan; Lawrence, Susan; Alexander, Roderick J.
Abstract: Aim: To give shielding Registrars opportunities to innovate and lead service development through telephone triage of Surgical Assessment Unit (SAU) referrals from General Practitioners and Nurse Practitioners. Prior to the COVID pandemic, referrals were taken by Nurse Coordinators. Increasing call volumes put pressure on the department and disrupted clinical duties. Furthermore, referrers often expressed difficulties in contacting SAU staff. Methods: During the study, referral calls were diverted for triage by the hospital switchboard. Three outcomes were offered: Clinical advice, 'Hot Clinic' (HC) appointment or urgent SAU review. Prospective referral data (15/6-31/7/2020) and retrospective non-triage data (15/6-1/7/2019) were gathered. Triage effects were measured by outcome comparison with non-triage data and the associated financial implications calculated. Stakeholder feedback questionnaires were distributed. Results: Non-triage data showed 56% of patients reviewed in SAU were sent home and 44% admitted, compared to 23.6% and 28.1% of referrals during the 2020 study period. Furthermore, 28.4% of admissions were avoided by triage. Only 3.1% of triaged patients presented to Emergency Department within 7 days of the triage conversation. Almost half of these had been reviewed in SAU following triage and discharged the same day. HC availability was limited during the triage study. In view of reduced admissions and overall cost savings of £8330.62/week, expanding these clinics may prove cost neutral. Triage was universally popular with stakeholders. Data will inform future development of Urgent and Emergency Care at our hospital. Conclusions: Traditional ways of working should be challenged. Novel approaches can be cost effective & positively impact patient care.